2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing outcomes after cardiopulmonary resuscitation in emergency department

Abstract: BACKGROUND:The outcome of cardiopulmonary resuscitation (CPR) may depend on a variety of factors related to patient status or resuscitation management. To evaluate the factors influencing the outcome of CPR after cardiac arrest (CA) will be conducive to improve the effectiveness of resuscitation. Therefore, a study was designed to assess these factors in the emergency department (ED) of a city hospital.METHODS:A CPR registry conforming to the Utstein-style template was conducted in the ED of the First Affiliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The success was attributed to immediate recognition, prompt CPR, oxygen therapy and fl uid therapy in that order. Other researchers have reported that witnessed arrests and shorter time of CPR were associated with higher survival rates when compared to unwitnessed arrests or a longer duration of resuscitation [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The success was attributed to immediate recognition, prompt CPR, oxygen therapy and fl uid therapy in that order. Other researchers have reported that witnessed arrests and shorter time of CPR were associated with higher survival rates when compared to unwitnessed arrests or a longer duration of resuscitation [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 725 patients, Xue et al demonstrated that 97.8% of patients with CPR lasting at least 15 min achieved ROSC, with a 36% survival to discharge and 20.2% favorable neurological outcomes. CPR more than 15 min was, however, associated with ROSC in only 15.7%, with a 2.5% survival to discharge and 0.8% favorable neurological outcomes [7]. A cutoff of 15 min as a predictor of ROSC and longer-term survival has been observed in many other studies.…”
Section: Impact Of Duration Of Cardio-pulmonary Resuscitationmentioning
confidence: 91%
“…A number of recent studies have demonstrated that prolonged cardio-pulmonary resuscitation (CPR) is associated with poor survival and neurological outcomes [4,[7][8][9]. In a study of 725 patients, Xue et al demonstrated that 97.8% of patients with CPR lasting at least 15 min achieved ROSC, with a 36% survival to discharge and 20.2% favorable neurological outcomes.…”
Section: Impact Of Duration Of Cardio-pulmonary Resuscitationmentioning
confidence: 97%
“…Therefore, the current clinical resuscitation research of focuses mainly on influencing the factors affecting the CPR outcomes and increasing the resuscitation effectiveness [10]. Cardiac etiology, shockable rhythms, CPR duration ≤ 15 min, and total adrenaline dose ≤ 5 mg were suggested as predictors of a favorable outcome, whereas traumatic etiology, previous terminal illness, or multiple organ failures were predictors of an unfavorable outcome [11].…”
Section: Introductionmentioning
confidence: 99%